Prison as a Heterotopia in the Roman "Berlin-Alexanderplatz" by Alfred Döblin - Yılmaz, Zennube Şahin (European Journal of Multidisciplinary Studies, 2018)
One of the biggest problems of modern times and modern literature is the big city. The big city problems are accepted as a motive of modern literature. These problems and the prison are concretized in the novel "Berlin-Alexanderplatz" by Alfred Döblin. The prison in the novel is taken with regard to Michel Foucault's heterotopic perspective or concept. On this occasion stands the relationship of the main character with the prison in the foreground in the analysis of the novel. The society is the origin of the mental problems of the figure seen in the novel. The figure is in a confrontation with society and actually with itself. Because of this, the complexity of the subject with society is taken into consideration by the perception of the city and the attempt to overcome the urban problems. The figure seeks for itself a space other than society. The prison is referred to as another room and the meaning of the prison is described as heterotopia. In addition, the novel is analyzed with Döblin's language or narrative style. Because the construction of the novel gives the narrator a special value. From the narrator, the heterotopic meaning of the prison is elucidated.
Keywords: Heterotopia -Prison, society, mental problems.